The Antecedent of teachers' intention to use e-learning during a pandemic: TAM approach - Hanafi Hanafi (Association for Scientific Computing Electrical and Engineering(ASCEE), 2021)
Many education institutions implement e-learning to replace traditional face-to-face teaching and learning activities due to the Covid19 pandemic. The situation forced students and teachers to adapt to the new normal of teaching and learning activities. This study aimed to evaluate the teachers' intention to use e-learning after almost a year after the Covid19 pandemic widespread began, using Technology Acceptance Model (TAM) approach. The partial Least Square-Structural Equation Model (PLS-SEM) technique was employed to evaluate the intention to use e-learning. Using 291 samples of Teachers in Indonesia, this study shows that the TAM approach describes the antecedent of teachers' intention to use e-learning during a pandemic. Perceived ease of use, perceived usefulness, and job relevance are determinant factors of teachers’ intention to use e-learning during the pandemic.